VALIDITAS E-MODUL MENULIS ARTIKEL ILMIAH BERBASIS GENRE BASED APPROACH/GBA - Afif Rofii; Ramli Ramli; Supriyati Supriyati; Imey Alviona Caesar (Universitas Batanghari, 2024)
This research sought to validate an e-module designed to facilitate scientific article writing, grounded in the Genre-Based Approach (GBA). A quantitative survey method was employed, utilizing a Likert-scale questionnaire to gather both quantitative and qualitative data. Four experts in their respective fields were involved in the validation process, assessing the e-module's content, presentation, language, and graphic feasibility. The results of the expert validation indicated that the e-module meets the criteria for a high-quality educational tool, aligning with the needs of students and the objectives of learning scientific article writing. Specifically, the content component received an overall average score of 4.46, classified as